Long-term variation and regulation of internal phosphorus loading in Loch Leven - Spears, Bryan Millar; Carvalho, L.; Perkins, Rupert Gordon; Kirika, A.; Paterson, David Maxwell (Hydrobiologia, 2012)
Long-term monitoring data (1968-2008) were used to investigate internal phosphorus (P) loading following external P loading reduction in shallow Loch Leven, Scotland. A whole-lake sediment P inventory (upper 3 cm of sediment; 2005) suggested a release-potential of 29.7 tonnes (t) from the release sensitive sediment P pools. 18.5 t was contained within shallow water sediments (< 4.5 m water depth) with 7.6 t in deeper water sediments below the photic zone (> 5 m water depth). The "observed" release (< 5.1 t), estimated using a water column P mass balance approach (1989-2008), was < 5.1 t, indicating the presence of regulating mechanisms. Observed P release declined between 1989 and 2008, with the exception of 2003-2006. Observed P release estimates were positively correlated with annual average water column P concentration after 1989, highlighting the role of internal loading in maintaining poor water quality conditions after management intervention. Multiple regression analysis suggested that internal loading was driven by the wave mixed depth in spring (positive driver), summer water temperature (positive driver) and spring water clarity transparency (negative driver). The potential importance of biological and physico-chemical feedback mechanisms in the regulation of benthic-pelagic coupling and water quality in Loch Leven are discussed.